2021
DOI: 10.1002/jor.25075
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of subchondral bone, cartilage, and synovium in naturally occurring equine palmar/plantar osteochondral disease

Abstract: Osteoarthritis (OA) is a disease of the entire joint but the relationship between pathological events in various joint tissues is poorly understood. We examined concurrent changes in bone, cartilage, and synovium in a naturally occurring equine model of joint degeneration. Joints (n = 64) were grossly assessed for palmar/plantar osteochondral disease (POD) in racehorses that required euthanasia for unrelated reasons and assigned a grade of 0 (n = 34), 1 (n = 17), 2 or 3 (n = 13) using a recognized grading sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…47 Many canonical pathways enriched by the plasma and synovial fluid EV DE miRNA putative target genes were essential for or related to PTOA pathogenesis, including the "OA pathway" and "rheumatoid arthritis pathway." Additionally, downstream targets of these signaling pathways with known roles in OA pathogenesis were identified for plasma EVs consisting of matrix MMP3, 48 MMP14, 49 a disintegrin and MMP with thrombospondin motifs 2, 50 and receptor tyrosine-protein kinase (ERBB4). 51 Synovial fluid EV-signaling pathway downstream targets included VEGF, 50 histone deacetylase 4, 52 and specificity protein 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Many canonical pathways enriched by the plasma and synovial fluid EV DE miRNA putative target genes were essential for or related to PTOA pathogenesis, including the "OA pathway" and "rheumatoid arthritis pathway." Additionally, downstream targets of these signaling pathways with known roles in OA pathogenesis were identified for plasma EVs consisting of matrix MMP3, 48 MMP14, 49 a disintegrin and MMP with thrombospondin motifs 2, 50 and receptor tyrosine-protein kinase (ERBB4). 51 Synovial fluid EV-signaling pathway downstream targets included VEGF, 50 histone deacetylase 4, 52 and specificity protein 1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, downstream targets of these signaling pathways with known roles in OA pathogenesis were identified for plasma EVs consisting of matrix MMP3, 48 MMP14, 49 a disintegrin and MMP with thrombospondin motifs 2, 50 and receptor tyrosine-protein kinase (ERBB4). 51 Synovial fluid EV-signaling pathway downstream targets included VEGF, 50 histone deacetylase 4, 52 and specificity protein 1. 53 In our study, fibrosis was the most significant canonical pathway identified from both plasma and synovial fluid EV DE miRNAs and their putative mRNAs targets.…”
Section: Discussionmentioning
confidence: 99%